2018
DOI: 10.1177/0091217417749789
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of stress, coping strategies, and life style in the development of breast cancer

Abstract: Objective The aim of the present study was to investigate the possibility of the effect of life long stressful events, along with coping method used, perception of social support, and life style on the development of breast cancer. Methods In this hospital-based case control study, the study group comprised 250 women with breast cancer who were followed by Florence Nightingale Breast Study Group. Control group included 250 women, who had similar sociodemographic characteristics to the study group. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…This status cannot be maintained for long periods, as the parasympathetic system restores equilibrium [1,2]. PS is experienced as a negative sensation and is associated with adverse health consequences, including increased cardiovascular risks, hypertension, cancer, social adversity, metabolic syndrome risk and insomnia [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This status cannot be maintained for long periods, as the parasympathetic system restores equilibrium [1,2]. PS is experienced as a negative sensation and is associated with adverse health consequences, including increased cardiovascular risks, hypertension, cancer, social adversity, metabolic syndrome risk and insomnia [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Yildirim et al [32] used a hospital-based case-control study of 250 cases treated for BC (surgery, chemotherapy, and radiotherapy), aged 27-64 years, to estimate PS influence on BC risk, applying semistructured interview, the Stress Evaluation Form, and the Healthy Lifestyle Behavior Scale. Lifelong stressful events such as childhood trauma (e.g., loss of mother or father, divorce of parents, or serious health problems), major life events (death of a loved one, serious disease, and divorce), chronic stressor (e.g., interpersonal relationship problems), and experience of stress within the last five years before disease were collected.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while a Japanese prospective study in over 100,000 participants did not find any association between short-term stress and cancer incidence, it revealed that men with higher perceived stress levels had an 11% greater risk of developing cancer than those with low stress levels, particularly in smokers, alcohol drinkers, obese subjects, and subjects without a family history of cancer [9]. A higher level of stress was also found to disturb neuro-immunological systems and the functions of the neuroendocrine axes, leading to changes in hormone levels in blood, which increased the risk of breast cancer [6,10]. Psychosocial stress was associated with an increased incidence of colorectal, lung, head and neck, hepatobiliary, esophagus [11], prostate [12], bladder, rectal, stomach [13], and lymphoid or hematopoietic cancers [4] in some recent studies.…”
Section: Chronic Stress and Cancermentioning
confidence: 99%